Neuromodulation directed at the prefrontal cortex of subjects with obesity reduces snack food intake and hunger in a randomized trial - Heinitz, Sascha (Am J Clin Nutr, 2017)
Background: Obesity is associated with reduced activation in the left dorsolateral prefrontal cortex (DLPFC), a region of the brain that plays a key role in the support of self-regulatory aspects of eating behavior and inhibitory control. Transcranial direct current stimulation (tDCS) is a noninvasive technique used to modulate brain activity. Objectives: We tested whether repeated anodal tDCS targeted at the left DLPFC (compared with sham tDCS) has an immediate effect on eating behavior during ad libitum food intake, resulting in weight change, and whether it might influence longer-term food intake–related appetite ratings in individuals with obesity. Design: In a randomized parallel-design study combining inpatient and outpatient assessments over 31 d, 23 individuals with obesity [12 men; mean ± SD body mass index (BMI; in kg/m(2)): 39.3 ± 8.42] received 15 sessions of anodal (i.e., enhancing cortical activity) or sham tDCS aimed at the left DLPFC. Ad libitum food intake was assessed through the use of a vending machine paradigm and snack food taste tests (SFTTs). Appetite was evaluated with a visual analog scale (VAS). Body weight was measured. We examined the effect of short-term (i.e., 3 sessions) and long-term (i.e., 15 sessions) tDCS on these variables. Results: Relative to sham tDCS, short-term anodal tDCS did not influence ad libitum intake of food from the vending machines. Accordingly, no effect on short-term or 4-wk weight change was observed. In the anodal tDCS group, compared with the sham group, VAS ratings for hunger and the urge to eat declined significantly more (P = 0.01 and P = 0.05, respectively), and total energy intake during an SFTT was relatively lower in satiated individuals (P = 0.01), after long-term tDCS. Conclusions: Short-term anodal tDCS of the left DLPFC did not have an immediate effect on ad libitum food intake or thereby weight change, relative to sham tDCS. Hunger and snack food intake were reduced only after a longer period of anodal tDCS in individuals with obesity. This trial was registered at clinicaltrials.gov as NCT00739362.